STRATEGI LAYANAN DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA DUMAI DALAM KEGIATAN STORYTELLING DI MASA NORMAL BARU - Hariadi, Agung; Defriyani, Rizca (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
The library service is the backbone of the library. Without services, the collection of library materials cannot be optimally utilized. One of the services provided by the Library and Archives Department of Dumai City is storytelling services. Storytelling service is a service conducted to convey a story through words, pictures, photos, or sound. Challenges arising from the impact of the pandemic have resulted in the library services being less optimal. Nevertheless, the Library and Archives Department of Dumai City strategically conducts activities as a form of prime service to library users through innovative storytelling services. The method used in this research is qualitative descriptive. Data collection is done through observation and survey, including direct field monitoring and interviews with the research subjects. The research results state that the strategy and innovation of storytelling service activities during the pandemic are effectively carried out online by utilizing social media. When there are policies related to easing activities in the new normal, face-to-face interactions can provide a very interesting impression and receive a very positive response, even when adhering to health protocols.